2019
DOI: 10.1080/1177083x.2018.1561476
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of safety improvement in New Zealand public hospitals

Abstract: Patient Safety is central to the New Zealand (NZ) health strategy. However international experience shows that safety improvement work frequently fails to meet its objectives. This article provides a qualitative account of the challenges of safety improvement from the perspective of nurses, doctors, and managers in three departments in two NZ public hospitals. These staff described significant tensions in relation to engagement and organisational capacity. An analysis of their perspectives through the Organisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Others are lax accident management techniques, safety bureaucracy leading to bottlenecks in safety matters and facilities not built to make evacuation easy. Beaver (2019) recommended safety improvement, which includes practices and implementation. The focus of this paper is on information necessary to develop the FSMP framework for public hospital buildings.…”
Section: Fire Safety Management Plan In Healthcare Buildingsmentioning
confidence: 99%
“…Others are lax accident management techniques, safety bureaucracy leading to bottlenecks in safety matters and facilities not built to make evacuation easy. Beaver (2019) recommended safety improvement, which includes practices and implementation. The focus of this paper is on information necessary to develop the FSMP framework for public hospital buildings.…”
Section: Fire Safety Management Plan In Healthcare Buildingsmentioning
confidence: 99%
“…While quality improvement is a fundamental competency for nurses practicing in New Zealand, they often do not feel well prepared to accomplish this task 10,11. In a qualitative study in 2 New Zealand hospitals where nurses, physicians, and managers were interviewed about their perspectives on quality improvement activities, nurses described themselves as “comprehensively involved.”12 (p118) Nevertheless, barriers for nurses completing quality improvement projects included the following: (1) lack of resources to the extent that projects were difficult to implement and only partially completed; inability to provide time release for nurses' involvement; (2) projects starting well and becoming neglected as priorities changed; and (3) lack of resources for projects that were not of apparent economic benefit. Based on outcomes of this qualitative study, the researchers concluded that, with some exceptions, staff felt little ownership of the improvement process, and those who engaged in these projects faced frustration and a risk of burnout 12.…”
Section: Introductionmentioning
confidence: 99%
“…Based on outcomes of this qualitative study, the researchers concluded that, with some exceptions, staff felt little ownership of the improvement process, and those who engaged in these projects faced frustration and a risk of burnout. 12 They further recommend ensuring adequate resources of time and expertise, as well as efforts to empower staff to take control of quality improvement processes.…”
Section: Introductionmentioning
confidence: 99%
“…An efficiently designed process still needs to be implemented on a daily basis by people. This research builds on the findings in the literature about the challenges of implementing change in hospitals and that there has been a lack of in-depth engagement with frontline staff about their experiences (Beaver, 2019;Johnston et al, 2016;Person et al, 2013;Rixon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to implementing change in the healthcare context are well known to those working in patient safety and quality improvement. Research into the challenges of implementing safety improvement initiatives in New Zealand hospitals highlights the importance of understanding cultural factors (Beaver, 2019). In addition to more dedicated resources and time to focus on improvement projects, staff need to be more empowered to take control of these projects within their localities.…”
Section: Opportunity For Systemic Reform In New Zealandmentioning
confidence: 99%